2009
DOI: 10.1080/13506280802151480
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for rapid development of colour–location binding in infants’ visual short-term memory

Abstract: Change-detection tasks reveal that infants’ ability to bind color to location in visual short-term memory (VSTM) develops rapidly: Seven-month-old infants, but not 6-month-old infants, detect that successive arrays of 3 objects are different if they contain the same colors in different locations (Oakes et al., 2006). Here we test a counterintuitive consequence of the hypothesis that six-month-old infants are unable to bind colors to locations: When comparing two successive stimulus arrays, these infants will o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 32 publications
11
55
4
Order By: Relevance
“…Infants' preference for changing arrays of three or four items might not require memory for all of the items, but instead draw on the successful storage of a subset or even just a single item, which-if combined across trials, would yield a significant preference for the changing array. However, Oakes, Messenger, Ross-Sheehy, and Luck (2009) found that when 6-month-old infants (who in earlier work exhibited successful change detection with a maximum of one item) were shown 3-item-displays in which all three items changed color on every iteration, infants still did not reliably look at the changing screen (for related findings, see Feigenson & Carey, 2005). This suggests that memory for a subset of an array is not sufficient to drive infants' visual preference in this task.…”
Section: Methodological Differences In Previous Studiesmentioning
confidence: 71%
“…Infants' preference for changing arrays of three or four items might not require memory for all of the items, but instead draw on the successful storage of a subset or even just a single item, which-if combined across trials, would yield a significant preference for the changing array. However, Oakes, Messenger, Ross-Sheehy, and Luck (2009) found that when 6-month-old infants (who in earlier work exhibited successful change detection with a maximum of one item) were shown 3-item-displays in which all three items changed color on every iteration, infants still did not reliably look at the changing screen (for related findings, see Feigenson & Carey, 2005). This suggests that memory for a subset of an array is not sufficient to drive infants' visual preference in this task.…”
Section: Methodological Differences In Previous Studiesmentioning
confidence: 71%
“…First, Oakes, Ross-Sheehy, and Luck (2006) showed that the ability to bind colors to locations in the preferential looking task coincided developmentally with the increase in capacity from 1 to 2 or more items at 7.5 months of age. As described above, Oakes et al (2009) showed that young infants did not prefer the changing stream at a set size of 3 even when all 3 items in the display changed with every blink. The authors interpreted this result as further evidence that infants must be able to bind colors to locations in order to remember more than 1 item simultaneously.…”
Section: Introductionmentioning
confidence: 88%
“…Perone, Simmering, and Spencer (2011) challenged this conclusion by showing that a computational model, with no mechanism for binding colors to space, can capture younger and older infants' performance in the critical conditions from Ross-Sheehy et al (2003) and Oakes et al (2009). The model proposed by Perone and colleagues (2011) suggests that infants' emerging ability to detect changes in displays with more than 1 item depends on their ability to stably remember the items on the no-change display as well as on the change display.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, neither provides a specific proposal for how or why capacity changes during childhood. Other researchers have put forth proposals, based on performance in a variety of working memory tasks, that focused on improvements in the functioning of existing memory systems (e.g., Gathercole, Pickering, Ambridge, & Wearing, 2004), cognitive control (e.g., Marcovitch, Boseovski, Knapp, & Kane, 2010), basic processes of object individuation/identification (e.g., Oakes, Messenger, Ross-Sheehy, & Luck, 2009), or neural connectivity (e.g., myelination; Case, 1995). Although each of these approaches has benefitted our understanding of children’s performance in a given task, none has provided a complete account of the processes underlying performance and developmental change.…”
Section: Developmental Increases In Capacitymentioning
confidence: 99%